EXPLORING STUDENT PERCEPTIONS: VISUALIZING ABSTRACT CONCEPTS IN DESCRIPTIVE GEOMETRY USING GEOGEBRA: Jawa Barat, Indonesia - Wijaksana, Aris Hadiyan; Yaya Sukjaya Kusumah; Turmudi (Jurnal Math-UMB.EDU, 2026)
Descriptive Geometry is a fundamental course that demands high-level spatial visualization skills, where students often face significant cognitive challenges in projecting three-dimensional (3D) objects onto two-dimensional (2D) planes using conventional methods. This study aims to deeply explore student perceptions regarding the use of the dynamic geometry software GeoGebra as a medium for visualizing abstract concepts in this course. Using a qualitative case study approach, this research involved 13 students from the mathematics education program at Universitas Negeri Jakarta. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that students perceive GeoGebra as a transformative pedagogical tool. Four main themes were identified: (1) GeoGebra serves as a conceptual bridge that translates abstract concepts into concrete and dynamic visual representations; (2) GeoGebra's interactive environment is considered far superior to the static paper-and-pencil method, offering accuracy, efficiency, and freedom to experiment; (3) The use of GeoGebra shifts the student's role from a passive recipient to an active learner engaged in independent exploration; and (4) Despite an initial learning curve, the challenge of mastering the software fosters the development of student agency and learning autonomy. This study concludes that GeoGebra effectively reduces the cognitive load associated with spatial visualization and enhances student engagement and conceptual understanding. The implications of these findings underscore the importance of planned technological integration into advanced geometry curricula to facilitate more meaningful learning. Keywords: Descriptive Geometry; GeoGebra; Spatial Visualization; Student Perceptions; Dynamic Geometry Software